For f(x) = 3x +1 and g(x) = x2 – 6, find (f- g)(x).

Answers

Answer 1
Answer:

Answer:

\boxed{\sf (f-g)(x) = -{x}^(2)  + 3x + 7}

Given:

\sf f(x) = 3x + 1 \n \sf g(x) =  {x}^(2)  - 6

To find:

\sf (f - g)(x) = f(x) - g(x)

Step-by-step explanation:

\sf \implies(f - g)x = f(x) - g(x) \n  \n \sf \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:    = (3x + 1) - ( {x}^(2)  - 6) \n  \n \sf \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:    = (3x + 1)  + (-  {x}^(2)  + 6) \n  \n \sf \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:    = 3x + 1 -  {x}^(2)  + 6 \n  \n \sf \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:    = - {x}^(2)  + 3x + 1 + 6 \n  \n \sf \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:    =  -{x}^(2)  + 3x + 7


Related Questions

Convert 18/5 to a mixed number
Any number that is divisible by 3 is also divisible by 6.Find a counterexample to show that the conjecture is false. 21182412
in one baseball season, Peter hit twice the difference of the number of home runs Alice hit and 6. Altogether, they hit 18 home runs. how many home runs did each player hit that season?
Let f(x) = x2 - 8x 5. Find f(-1).
Find the least common denominator (LCD) of7/12 and 3/2

Money adding how to do it

Answers

Basically if you know your addition just add the values of each coin or dollar bill. Just forget about the $ sign or cent sign when adding the values together.
FOR EXAMPLE:
$1 and $2.75
You would ignore dollar sign and add together like normal to get
3.75
But remember to add dollar sign back at the end.
If the value only have 2 values with cents it should be something like
0.54 cents BUT NO DOLLAR SIGN
Hope that helps
what you do is add the numbers up then when you get your answer put the dollar sign in the front of of the first number to the left hope that helps

Emily is making bows using ribbon. She has two pieces of ribbon to use. One is 23 yards long. The other is 4 1/4 yards long. She need 1 5/6 yards of ribbon to make each bow. What is the greatest number of bows emily can make? Show your work

Answers

Answer:

14


Step-by-step explanation:

In total, Emily has  23+4(1)/(4)=27(1)/(4)=(109)/(4)  yards of ribbon.

Each bow requires  1(5)/(6)=(11)/(6)  yards of ribbon


To figure out, we divide total amount of ribbon by amount each bow needs:

Number of bows = ((109)/(4))/((11)/(6))=14.86


So the maximum number of "complete" bows Emily can make is 14

Final answer:

Emily has a total of 27 1/4 yards of ribbon. Each bow requires 1 5/6 yards, therefore Emily can make 14 bows with the ribbon she has.

Explanation:

To solve this problem, we first need to determine the total amount of ribbon that Emily has. She has one piece that is 23 yards long and another that is 4 1/4 yards long. To find the total, we add these two lengths together:

23 yards + 4 1/4 yards = 27 1/4 yards

Each bow Emily makes needs 1 5/6 yards of ribbon. To find out how many bows she can make, we divide the total amount of ribbon by the amount needed for each bow:

27 1/4 yards ÷ 1 5/6 yards = 14.6(around)

Since Emily cannot make a fraction of a bow, we round down to the nearest whole number. So, Emily can make 14 bows.

Learn more about Division here:

brainly.com/question/2273245

#SPJ3

The function f(t) = 4t2 − 8t + 7 shows the height from the ground f(t), in meters, of a roller coaster car at different times t. Write f(t) in the vertex form a(x − h)2 + k, where a, h, and k are integers, and interpret the vertex of f(t).f(t) = 4(t − 1)2 + 3; the minimum height of the roller coaster is 3 meters from the ground
f(t) = 4(t − 1)2 + 3; the minimum height of the roller coaster is 1 meter from the ground
f(t) = 4(t − 1)2 + 2; the minimum height of the roller coaster is 2 meters from the ground
f(t) = 4(t − 1)2 + 2; the minimum height of the roller coaster is 1 meter from the ground

Answers

f(t) = 4t² - 8t + 7

f(t) = 4(t² - 2t) + 7
f(t) - 7 = 4(t² - 2t - __)

t² ⇒ t * t
2t ⇒ 2 * 1t
1² ⇒ 1 * 1

f(t) - 7 + 4(1) = 4(t² - 2t + 1)

(t-1)(t-1) = t(t-1) -1(t-1) = t² - t - t + 1 = t² - 2t + 1

f(t) = 4(t-1)² + 3 

Answer:

A f(1) =4(1)^2 – 8(1) +7 min height 3

Step-by-step explanation:

The function is a parabola, and the problem asks to transform the equation into f(t)=a(x-h)2 + k

Given f(t) = 4t2 -8t +7

= (4t2 - 8t + 4) + 7 - 4

=4 (t2 - 2t + 1) + 3

= 4 (t-1) 2 +3

This removes C and D from the viable choices.

Differentiating the f(t),

f’(t) = 8t – 8, the maximum/minimum value occurs at f’(t) = 0

0 = 8t – 8

t = 1

determining if maximum or minimum, f”(t) > 0 if minimum, f”(t) < 0 maximum

f”(t) = 8 > 0, therefore minimum

f(1) =4(1)^2 – 8(1) +7

= 3

Therefore, minimum height is 3.

The terminal side of an angle θ in standard position passes through the point (3, 1). Calculate the exact values of the six trig functions for angle θ.

Answers

Answer:

sin α = (y)/(r) = (1)/(√(10) )

cos α = (x)/(r) = (3)/(√(10) )

tan α = (y)/(x) = (1)/(3)

cot α = (x)/(y) = (3)/(1)

sec α = (r)/(x) = (√(10) )/(3)

csc α = (r)/(y) = (√(10) )/(1)

Step-by-step explanation:

If the point is given on the terminal side of an angle, then:

Calculate the distance between the point given and the origin:

r = √(x^2+y^2)

Here it is: √(3^2+1^2) = √(9+1) = √(10)

So we have:

x = 3

y = 1

r = √(10)

Now we can calculate all 6 trig, functions:

sin α = (y)/(r) = (1)/(√(10) )

cos α = (x)/(r) = (3)/(√(10) )

tan α = (y)/(x) = (1)/(3)

cot α = (x)/(y) = (3)/(1)

sec α = (r)/(x) = (√(10) )/(3)

csc α = (r)/(y) = (√(10) )/(1)

Final answer:

The question involves calculating the six trigonometric functions (Sin, Cos, Tan, Csc, Sec, Cot) for an angle in standard position with its terminal side passing through point (3,1). We find opposite and adjacent sides from the point's coordinates, the hypotenuse from Pythagoras' theorem, and calculate each ratio accordingly.

Explanation:

In the context of the problem, the point (3,1) specifies the terminal side of angle θ in standard position. This point is effectively the definition of your right triangle's opposite (y) and adjacent (x) sides in the trigonometric calculation, with the hypotenuse (h) obtained from Pythagoras' Theorem (h² = y² + x²). In this case, we get h = sqrt(3² + 1²) = sqrt(10).

The six trigonometric functions are defined as follows for this scenario:

  • Sin θ = y/h = 1/sqrt(10).
  • Cos θ = x/h = 3/sqrt(10).
  • Tan θ = y/x = 1/3.
  • Csc θ = 1/sin θ = sqrt(10).
  • Sec θ = 1/cos θ = sqrt(10)/3.
  • Cot θ = 1/tan θ = 3.

Learn more about Trigonometric Functions here:

brainly.com/question/28483432

#SPJ3

Identify all of the square roots of perfect squares in the list below. Select all that apply. A) √25 B) √36 C) √50 D) √144 E) √200 F) √362

Answers

Answer:

The square roots of perfect squares in the list are:

A) √25 = 5 B) √36 = 6 D) √144 = 12

The other numbers © √50, E) √200, and F) √362 are not square roots of perfect squares. Therefore, the correct answers are A, B, and D.

(-7x²-7x-7)-[(7x³-9x²-20)+(4x-11)]]=?(5x⁴+8x²+2)+7(5x⁴-3x²)=?
Please explain the work behind the solution

Answers

(-7x^2-7x-7)-[(7x^3-9x^2-20)+(4x-11)]]=\n=-7x^2-7x-7-(7x^3-9x^2-20+4x-11)=\n=-7x^2-7x-7-7x^3+9x^2+20-4x+11=-7x^3+2x^2-11x+24\n\n (5x^4+8x^2+2)+7(5x^4-3x^2)=5x^4+8x^2+2+35x^4-21x^2=\n=39x^4-13x^2+2